Digestibility of Tilapia (Oreochromis niloticus) Feed with the Addition of Gude Bean Flour (Cajanus cajan). - Nurhalisa, Wida; Lumbessy, Salnida Yuniarti; Lestari, Dewi Putri (Universitas Malikussaleh, 2022)
The purpose of this study was to analyze the protein and fiber digestibility of tilapia (O. niloticus) with the addition of gude (C. cajan) flour. The research method used in this study was an experiment using a Completely Randomized Design (CRD). The treatment used consisted of 4 treatments and 3 replications, namely: Gude Bean Flour 0% (control) (P0), 10% (P1), 20% (P2), and 30% (P3). Parameters measured included protein digestibility, fiber digestibility, absolute weight growth, absolute length growth, specific growth rate (SGR), feed conversion ratio (FCR), feed efficiency, and survival. Data were analyzed between treatments by analysis of variance (Anova) and differences between treatments by Duncan's test. The results showed that the addition of different concentrations of gude bean flour to feed could affect protein digestibility and growth in feed but did not affect fiber digestibility, feed conversion ratio (FCR), feed efficiency (EPP), and life expectancy of tilapia. The addition of 10% gude flour concentration gave the best results with an absolute weight growth value of 19.08 g, and an absolute length of 5.60 cm even though it had the same level of protein digestibility as the control treatment